Verbal Auditory Cueing of Improvisational Dance: A Proposed Method for Training Agency in Parkinson’s Disease - Batson, Glenna; Hugenschmidt, Christina E.; Soriano, Christina T. (Frontiers in Neurology, 2016)
Dance is a non-pharmacological intervention that helps maintain functional independence and quality of life in people with Parkinson’s disease (PPD). Results from controlled studies on group-delivered dance for people with mild-to-moderate stage Parkinson’s have shown statistically and clinically significant improvements in gait, balance, and psychosocial factors. Tested interventions include non-partnered dance forms (ballet and modern dance) and partnered (tango). In all of these dance forms, specific movement patterns initially are learned through repetition and performed in time to music. Once the basic steps are mastered, students may be encouraged to improvise on the learned steps as they perform them in rhythm with the music. Here, we summarize a method of teaching improvisational dance that advances previous reported benefits of dance for people with PD. The method relies primarily on improvisational verbal auditory cueing (VAC) with less emphasis on directed movement instruction. This method builds on the idea that daily living requires flexible, adaptive responses to real-life challenges. In PD, movement disorders not only limit mobility, but also impair spontaneity of thought and action. Dance improvisation trains spontaneity of thought, fostering open and immediate interpretation of verbally delivered movement cues. Here we present an introduction to a proposed method, detailing its methodological specifics, and pointing to future directions. The viewpoint advances an embodied cognitive approach that has eco-validity in helping PPD meet the changing demands of daily living.